Stimulasi Kecerdasan Linguistik Anak Usia Dini melalui Pembelajaran Bahasa Arab - Hasan, Laili Mas Ulliyah; Adhimah, Syifaul; Rido'i, Muhammad (Study Program of Arabic Language Teaching, 2024)
Linguistic intelligence is an essential verbal skill that children, including those in early childhood, should possess. This study explores the stimulation of linguistic intelligence in early childhood through Arabic language learning at RA Mamba’ul Hisan Surabaya. The research employs a qualitative phenomenology and descriptive study methodology, with subjects including children aged 5-6 years and their teachers. Data collection techniques include observation and documentation. Observations are conducted to see how children engage with Arabic language learning activities such as watching animated videos, using interactive learning applications, storytelling, and singing Arabic songs. Documentation includes collecting children's work and recording their learning sessions. Data analysis uses a phenomenological approach to understand the lived experiences of the children and teachers. The analysis process involves bracketing (setting aside the researcher's preconceptions), describing (providing a detailed description of the observed phenomena), analyzing (identifying significant statements and themes), and synthesizing (integrating themes to form a comprehensive understanding). The findings indicate that stimulating linguistic intelligence in early childhood through Arabic language learning—watching animated videos, using interactive learning applications, storytelling, and singing songs in Arabic—is effective for children aged 5-6 years. Children show high enthusiasm when watching Arabic animated videos, listening to and singing songs, and listening to stories in Arabic. They can remember new vocabulary and understand the meaning of words in the context of stories conveyed through animation and songs. Interactive learning applications provide a fun learning experience, with children actively participating in games featuring hijaiyyah letters and simple vocabulary, helping them recognize and remember these words easily. The effectiveness of these methods is high due to engaging visual, auditory, and kinesthetic stimuli.